Morphological/pathogenic variability of Fusarium verticillioides in La Ciénega/Chapala, Mexico and inoculation techniques evaluation - Zacamo-Velázquez, Norma Y. (2022)
Introduction. Corn ear rot caused by Fusarium verticillioides (F. verticillioides) is one of the most important diseases in the world. In Mexico it causes losses of up to 30 %. The increase in the levels  of this disease in the last years requires inspections in producing areas to identify the main strains that damage the grain. Objectives. To determine the morphological and pathogenic variability of F. verticillioides isolates from corn samples from the corn producing area of La Ciénega/Chapala, Mexico, and to identify the best technique for inoculating the pathogen in ears. Materials and Methods. Twenty isolates of F. verticillioides were obtained from samples of corn kernels with disease symptoms. The isolates were used to inoculate, with the use of different inoculation techniques, developing corn cobs (R2) of P-3057 cultivated in Tepatitlán, Jalisco during the Spring/Summer 2019 agricultural cycle under rainfed conditions. The incidence and severity of the disease (SDI) of the isolates and the microscopic morphology of the strains were evaluated. Results. F. verticillioides isolates differed in colony color, mycelial type, abundance, and vegetative mycelial coloration. The incidence and severity were statistically different between F. verticillioides isolates and inoculation techniques tested. Interaction between isolates and inoculation technique was observed. The disease incidence showed values of 82 and 95% with aspersion and toothpick inoculation techniques, respectably. The SDI varied between 8 and 15.5 % with the aspersion and toothpick techniques, in that order. Conclusions. F. verticillioides strains showed variability for pathogenicity and severity of infection. Pathogenicity was related to the inoculation technique used. The toothpick inoculation technique was the one that presented the highest incidence and severity of infection.